Reframing Perilaku Penyalahgunaan Aset dalam Kacamata Fraud Triangle: Sebuah Studi Fenomenologis - Ruri Octari Dinata; Tri Utami Lestari; Hilda Salman Said (Owner : Riset dan Jurnal Akuntansi, 2026)
This study examines a case of asset misappropriation that occurred in a subsidiary of a state-owned enterprise in West Java by exploring behavioral factors as the basis of motives, the perpetrators’ modus operandi, and the resulting losses. A qualitative method with a phenomenological approach is employed to understand the phenomenon of asset misappropriation from the perspective of organizational actors’ lived experiences. This study was conducted in a subsidiary of a state-owned enterprise, referred to as PT Aman Sejahtera (pseudonym), employing interviews and observations within a phenomenological approach. This study contributes by extending fraud theory through a phenomenological lens that emphasizes behavioral memory and motivation as central mechanisms of asset misappropriation. The findings indicate that asset misappropriation at PT. Aman Sejahtera cannot be understood merely as a consequence of procedural weaknesses or deficiencies in internal control, but rather as a behavioral phenomenon shaped by cognitive processes, individual experiences, and motivations within the organization. Employees’ perceptions of deviant behavior are influenced by organizational culture, prior experiences, and social interactions, which subsequently shape judgment and decision-making processes involving ethical considerations, personal risk, and structural relations. Internalized experiences and knowledge form behavioral memories that may either normalize or prevent asset misappropriation, while individual motivation serves as a key link between knowledge and action. These findings emphasize that preventing asset misappropriation requires not only the strengthening of systems and procedures, but also the development of ethical awareness, a healthy organizational culture, and a more humanistic, behavior-oriented accounting approach.